Letter - Winstanley, E.
032-0112-001 Mr. Bell TELEGRAPHIC ADDRESS: INLAND-"WHOLESALE, MANCHESTER." FOREIGN-"COPEXPORT, MANCHESTER." TELEPHONE: BLACKFRIARS 1212. EXTENSION NO. 87 PLEASE ADDRESS YOUR REPLY: CO-OPERATIVE WHOLESALE SOCIETY LIMITED, EXPORTERS, BUYING AND SHIPPING AGENTS, 1, BALLOON STREET, MANCHESTER, 4. CABLE CODES: A.B.C. 6TH AND 7TH EDITIONS; WESTERN UNION 8 LETTER; BENTLEY COMPLETE PHRASE; BENTLEY SECOND PHRASE; A.1. MARCONI, AND PRIVATE. Our Reference: Export 2185 ST/HP. Your Reference: 1st February, 1939. The Trades Union Congress, Transport House, Smith Square, LONDON S.W.1. Dear Sirs, In accordance with our telephonic conversation with you yesterday, we have made arrangements to ship by s.s. CWS PROGRESS from Garston to Rouen tomorrow, the balance of the potatoes which were short shipped from the previous voyage. We have asked our Rouen Office to apply for disposal instructions to Mr. Schevenels of the Federation of Trade Unions, Paris. Yours faithfully, E. Winstanley Export Department. E.A.B. 292/946/32/112